Effectiveness of Regional Policies and Strategies in The Management of Household Waste and Waste A Kind in Bakalan Village, Polokarto District Sukoharjo District - Ichlasul Alfian Haqi; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2023)
The waste problem in Indonesia is of concern to the government because waste processing and management in Indonesia is below standard. In this case, the central government mandates that each region prepare a Regional Policy and Strategy (JAKSTRADA) for the management of household waste and similar waste based on this. By 2025, JAKSTRADA has a target of reducing household waste and similar waste by 30% and waste handling by 70%. This research aims to determine: 1) An overview of the management of household waste and similar waste in Bakalan Village, Sukoharjo Regency. 2) The effectiveness of Sukoharjo Regent Regulation Number 57 of 2018 concerning the management of household waste and similar waste in Bakalan Village, Sukoharjo Regency. The results of this research show that the effectiveness of JAKSTRADA according to the five indicators of legal effectiveness, namely legal factors, law enforcement factors, facilities and facilities factors, community factors, and cultural factors can be said to be ineffective. The obstacles encountered in achieving the effectiveness of JAKSTRADA are: 1) lack of intensive outreach 2) people who ignore household waste management 3) lack of facilities and facilities to support waste management.